Synthesis of Multiple Hydrogen-Bonded Unit Containing Polymer via Acyclic Diene Metathesis (ADMET) Polymerization of Oligoamide Monomer with Grubbs-Type Olefin Metathesis Catalysts - Luo1, K.; Pan1, X.S.; Yang1, Y.A.; Chen1, C. (Asian Journal of Chemistry, 2014)
The multiple hydrogen-bonded unit containing polymer was synthesized by using acyclic diene metathesis polymerization of oligoamide monomer with Grubbs-type olefin metathesis catalysts. The polymer was characterized by nuclear magnetic resonance, gel permeation chromatography and scanning electron microscope. The results demonstrate the successful synthesis of novel polymer via acyclic diene metathesis polymerization and the hydrogen-bonding-assisted formation of aggregates.